2017
DOI: 10.1021/acs.jpcc.7b00896
|View full text |Cite
|
Sign up to set email alerts
|

Surface Structure, Morphology, and Stability of Li(Ni1/3Mn1/3Co1/3)O2 Cathode Material

Abstract: Layered Li(Ni 1−x−y Mn x Co y )O 2 (NMC) oxides are promising cathode materials capable of addressing some of the challenges associated with next-generation energy storage devices. In particular, improved energy densities, longer cycle-life, and improved safety characteristics with respect to current technologies are needed. However, sufficient knowledge on the atomic-scale processes governing these metrics in working cells is still lacking. Herein, density functional theory (DFT) is employed to predict the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 45 publications
7
119
0
Order By: Relevance
“…The UEB framework allows us to understand how varying the surface termination through synthesis conditions or coating the surface with an interfacial layer will impact the material work function and surface band bending. The ability to model and understand these effects will help inform the emerging field of electrode–electrolyte interfacial engineering . The ability to understand surface versus bulk electrochemical descriptions and the depth of surface band bending within the UEB framework will aid the understanding of the electrochemical behavior of emerging nanoscale electrode materials .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UEB framework allows us to understand how varying the surface termination through synthesis conditions or coating the surface with an interfacial layer will impact the material work function and surface band bending. The ability to model and understand these effects will help inform the emerging field of electrode–electrolyte interfacial engineering . The ability to understand surface versus bulk electrochemical descriptions and the depth of surface band bending within the UEB framework will aid the understanding of the electrochemical behavior of emerging nanoscale electrode materials .…”
Section: Discussionmentioning
confidence: 99%
“…For example, stabilizing the <100> surface of α‐MnO 2 is predicted to shift the conduction band edge, and therefore the cation insertion potential, from 3 to ≈4 V versus Li/Li + , whereas stabilizing one of the <110> surfaces (labeled <110> c) is predicted to shift the cation insertion potential to ≈2 V versus Li/Li + as depicted in Figure a. The application of surface engineering in this spirit has been demonstrated in parallel with the UEB framework development, for instance in β‐MnO 2 , LiNi 0.5 Mn 1.5 O 4 , LiMn 2 O 4 , and Li(Ni 1/3 Mn 1/3 Co 1/3 )O 2 . In each of these studies, the stability and rate performance of cathode materials were identified to depend on the crystal facets exposed to the electrolyte, and structural changes were identified to improve performance.…”
Section: Exploiting Surface Engineering To Influence Electrochemical mentioning
confidence: 95%
“…Previously, DFT calculations reported that the equilibrium shapes of layered NMC particles are enclosed by three families of facets, namely (104), (001), and (012). 26 Among them, the surface energy of (012) and (104) is the highest and lowest, respectively, suggesting that they are the least and most thermodynamically favorable surfaces. Our recent theory-based studies showed that the surface fraction of each facet can be inuenced by the chemical potentials of oxygen and lithium during synthesis.…”
Section: Synthesis Of Nmc Single-crystal Samplesmentioning
confidence: 99%
“…As the (001) surface is parallel to the TM layers, it is impermeable to Li. 26,27 On the other hand, the (012) surface has efficient Li diffusion pathways. The net result is that particles with a large (001) surface tend to have lower utilization and capacity but better stability as compared to the sample with the (012) surface.…”
Section: Impact Of the Nmc Surface Facetmentioning
confidence: 99%
See 1 more Smart Citation